2020
DOI: 10.12659/msm.925051
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Significance of CA125 Dynamic Change for Progression Free Survival in Patients with Epithelial Ovarian Carcinoma

Abstract: Background This study aimed to investigate the value of CA125 dynamic change in PFS prediction for patients with epithelial ovarian carcinoma (EOC). Material/Methods Data analysis was performed using SPSS 24.0 statistical software with progression-free survival (PFS) as an outcome measure. Kaplan-Meier method was used to analyze the relationship between PFS and preoperative and postoperative NLR, PLR and CA125 levels, CA125 half-life, CA125-negative time, age, FIGO stag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Cancer antigen 125 (CA-125) is the most widely used marker in the management of patients with epithelial OC (EOC), and can be used as a predictive factor of overall survival (OS) in patients with EOC [ 6 ]. Since the time of Rudolf Virchow, who studied solid tumours and their microenvironment, several studies have shown that inflammation is associated with cancer and it is considered the seventh hallmark of cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cancer antigen 125 (CA-125) is the most widely used marker in the management of patients with epithelial OC (EOC), and can be used as a predictive factor of overall survival (OS) in patients with EOC [ 6 ]. Since the time of Rudolf Virchow, who studied solid tumours and their microenvironment, several studies have shown that inflammation is associated with cancer and it is considered the seventh hallmark of cancer [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The study by Liao et al [10], on the other hand, focused on OC patients who underwent surgery followed by chemotherapy, and the findings suggested that OC patients with a CA125 normalization time of more than 60 days had a poor prognosis. Furthermore, some authors have introduced the concept of CA125 half-life, demonstrating that it is an independent risk factor [11].…”
Section: Ca125mentioning
confidence: 99%